Fundamental properties of high-quality carbon nanofoam: from low to high density - Frese, Natalie; Taylor Mitchell, Shelby; Neumann, Christof; Bowers, Amanda; Gölzhäuser, Armin; Sattler, Klaus (Beilstein Journal of Nanotechnology, 2016)
Highly uniform samples of carbon nanofoam from hydrothermal sucrose carbonization were studied by helium ion microscopy (HIM), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. Foams with different densities were produced by changing the process temperature in the autoclave reactor. This work illustrates how the geometrical structure, electron core levels, and the vibrational signatures change when the density of the foams is varied. We find that the low-density foams have very uniform structure consisting of micropearls with ≈2–3 μm average diameter. Higher density foams contain larger-sized micropearls (≈6–9 μm diameter) which often coalesced to form nonspherical μm-sized units. Both, low- and high-density foams are comprised of predominantly sp2-type carbon. The higher density foams, however, show an advanced graphitization degree and a stronger sp3-type electronic contribution, related to the inclusion of sp3 connections in their surface network.
Keywords: carbon nanofoam; helium ion microscopy; hydrothermal carbonization; nanocarbons